METTL16 controls airway inflammations in smoking-induced COPD via regulating glutamine metabolism - Xinyu Jia; Shan Liu; Chunan Sun; Manni Zhu; Qi Yuan; Min Wang; Tingting Xu; Zhengxia Wang; Zhongqi Chen; Mao Huang; Ningfei Ji; Mingshun Zhang (Ecotoxicology and Environmental Safety)
The persistent airway inflammation is the main characteristic of chronic obstructive pulmonary disease (COPD), typically caused by an indoor environment pollution cigarette smoke (CS). METTL16 is an m6A methyltransferase that has been proven to be closely associated with the occurrence of various diseases. However, its exact role in smoking-induced COPD remains to be investigated. In this study, we found that the level of METTL16 was aberrantly decreased in lung tissues of COPD smokers. Similarly, murine model induced by CS and lung epithelial cell model induced by cigarette smoke extract (CSE) also confirmed this discovery. Moreover, in the Mettl16-deficient (Mettl16+/-) mice challenged with CS, airway inflammation was aggravated. To identify the potential target genes and regulatory pathways through METTL16, methylated RNA immunoprecipitation sequencing (meRIP-seq), RNA sequencing (RNA-seq) and metabolomic profiling were used. Knockdown of METTL16 significantly reduced the stability of glutamic-oxaloacetic transaminase 2 (GOT2) and downregulated its expression through m6A modification, while reprogramed glutamine metabolism in lung epithelial cells. Significant reduction in inflammation levels was observed in the 3-month COPD murine model fed a glutamine-supplemented diet. Mechanistically, METTL16 could regulate lung epithelial mitochondrial function by participating in the reprogramming of glutamine metabolism. Our study characterized the role of the METTL16/GOT2/glutamine axis in the occurrence and development of COPD, and emphasized the potential value of METTL16 and glutamine in the therapy of chronic airway inflammation in smoking-induced COPD.